LOOKING FOR A MEDIA BUSINESS MODEL - René Jara Reyes; Antoine Faure; Nicolás Del Valle Orellana (Brazilian Journalism Research, 2023)
ABSTRACT – This paper seeks to understand the undergoing digital transformations of the Chilean media system, based on the gaps, challenges, and opportunities that are currently facing the industrial and commercial organization of native digital media in Chile. In the Chilean case, the emergence of native digital media was developed with the new media business models in a context of a crisis of traditional modes of media financing. To study this process, we propose a descriptive-exploratory study focusing on six paradigmatic cases based on a campaign of semi-structured interviews (12) and a platform biography (6) to gather information on the structures, dynamics, and evolution of business models in the journalistic sites of these digital native media. Semi-structured interviews with founders/owners (FD) and monetization managers (MM), allow us to understand the reasons and objectives that underpin these transformations. Our sample is composed of six Chilean native digital media, which are legally registered in the relevant national information system in the Chilean public sphere (Reuters, 2022). The results of this analytical exercise show the tensions that occur in the business model’s five key dimensions: sustainability, innovation, associativity, community building, and journalistic added value. Towards the end, we list the study’s limitations and the understanding of the development of digital native media in Chile.